2001
DOI: 10.1016/s0014-5793(01)02946-5
|View full text |Cite
|
Sign up to set email alerts
|

Cycloprodigiosin hydrocloride suppresses tumor necrosis factor (TNF) α‐induced transcriptional activation by NF‐κB

Abstract: Cycloprodigiosin hydrochloride (cPrGW WHCl) obtained from a marine bacterium Pseudoalteromonas denitrificans induces apoptotic cell death in various cancerous cell lines. cPrGW WHCl alone caused a little cytotoxicity in HeLa cells, but it enhanced the apoptotic process progressively when co-administered with tumor necrosis factor (TNF)K K. Here we studied the effect of cPrGW WHCl on TNFK K-induced activation of the transcription factor nuclear factor U UB (NF-U UB). Luciferase gene reporter assays revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…For example, cPrGHCl suppresses activation of NF-B and AP-1, transcription factors involved in cell survival and proliferation, through unknown mechanisms unrelated to H þ / Cl À symporter activity. 17,18) We found here for the first time that cPrG-HCl has survival-promoting effects in PC12 cells. cPrG-HCl activates the Ras-PI3K-Akt pathway and suppresses y To whom correspondence should be addressed.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…For example, cPrGHCl suppresses activation of NF-B and AP-1, transcription factors involved in cell survival and proliferation, through unknown mechanisms unrelated to H þ / Cl À symporter activity. 17,18) We found here for the first time that cPrG-HCl has survival-promoting effects in PC12 cells. cPrG-HCl activates the Ras-PI3K-Akt pathway and suppresses y To whom correspondence should be addressed.…”
mentioning
confidence: 61%
“…Indeed, cPrG-HCl progressively enhances TNF-induced apoptosis by suppressing the transcriptional activity of NF-B. 17) Since the suppression of NF-B activity induces sustained JNK activity, which leads to apoptosis, [24][25][26] cPrG-HCl might promote cell death through sustained activation of JNK, accompanied by suppression of NF-B. We found that cPrG-HCl suppressed NF-B activation in PC12 cells and led to sustained JNK activity (data not shown).…”
Section: Cprg-hcl Suppresses Protein Synthesis Inhibitioninduced Apopmentioning
confidence: 79%
“…3,4 Cycloprodigiosin, another member of the prodigiosin family, induces apoptosis in various cancer cell lines including acute human T-cell leukemia, 17 promyelocytic leukemia, 18 human and rat hepatocellular cancer, 19 human breast cancer, 20 and TNF-stimulated human cervix carcinoma (HeLa). 21 The National Cancer Institute (Bethesda) has also shown that prodigiosin has an average IC 50 of 2.1 mM against a panel of 57 different human cancer cell lines (this information is available on the Internet at www.dtp.nci.nih.gov the NSC number for prodigiosin is 47147-F). Interestingly, we demonstrate in this paper that prodigiosin induces apoptosis in B-CLL cells with an IC 50 of 116725 nM.…”
Section: Discussionmentioning
confidence: 99%
“…PNU156804 blocks IL-2-dependent NF-kB and AP-1 activation 26 and it is a selective inhibitor of Janus tyrosine kinase 3 (Jak3). 27 Cycloprodigiosin also inhibits NF-kB activation, 21 although prodigiosin does not. 23 Taken together, these results suggest that inhibition of these signaling pathways cannot explain the apoptotic activity of prodigiosins in B and T lymphocytes.…”
Section: Prodigiosin Induces Apoptosis Of B-cll Cellsmentioning
confidence: 99%
“…7) Here we report that cPrG · HCl also suppresses the activation of AP-1 without affecting the upstream MAPK group; the suppression was not related to H ϩ /Cl Ϫ symporter activity.…”
Section: /Clmentioning
confidence: 59%